Mechanism of the Antihypertensive and Vasorelaxant Effects of the Flavonoid Tiliroside in Resistance Arteries - Silva, Grazielle C.; Pereira, Aline C.; Rezende, Bruno A.; da Silva, José P. Felippe; Cruz, Jader S.; de Souza, Maria de Fátima V.; Gomes, Roosevelt A.; Teles, Yanna C. F.; Cortes, Steyner F.; Lemos, Virginia S. (Planta Medica, 2013)
Hypertension is a leading cause of death and disability globally, and its prevalence continues to accelerate. The cardiovascular effects of the flavonoid tiliroside have never been reported. In this work, using complementary in vivo and in vitro approaches, we describe the antihypertensive effect of tiliroside and the underlying mechanisms involved in the reduction of blood pressure. Tiliroside (1, 5 or 10 mg/kg) induced a dose-dependent long-lasting decrease in blood pressure in conscious DOCA-salt hypertensive rats that was accompanied by an increased heart rate. Tiliroside also induced a concentration-dependent vasodilation of mesenteric resistance arteries precontracted with phenylephrine. Removal of the endothelium or pretreatment of the preparation with L-NAME or indomethacin did not modify the vasodilator response for tiliroside. When vessels were precontracted with a high K+ (50 mM) solution, tiliroside exhibited a vasodilator effect similar to that observed in vessels precontracted with phenylephrine. Experiments carried out in nominally Ca2+-free solution showed that tiliroside antagonized CaCl2-induced contractions. Moreover, tiliroside reduced the rise in intracellular Ca2+ concentration induced by membrane depolarization in vascular smooth muscle cells. Finally, tiliroside decreased the voltage-activated peak amplitude of the L-type Ca2+ channel current in freshly dissociated vascular smooth muscle cells from mesenteric arteries. Altogether, our results point to an antihypertensive effect of tiliroside due to a reduction in peripheral resistance through blockage of voltage-activated peak amplitude of the L-type Ca2+ channel in smooth muscle cells.
Keywords: flavonoids; tiliroside; antihypertensive effect; vasodilation; mesenteric artery; CaV 1.2